Effect of the histone deacetylase inhibitor resminostat on head and neck squamous cell carcinoma cell lines. Issue 5 (7th February 2017) - Enzenhofer, Elisabeth; Kadletz, Lorenz; Stanisz, Isabella; Kotowski, Ulana; Seemann, Rudolf; Schmid, Rainer; Thurnher, Dietmar; Heiduschka, Gregor
ABSTRACT: Background: Carcinogenesis is determined by various epigenetic events, such as histone deacetylation. The purpose of this study was to investigate the effect of the new histone deacetylase inhibitor resminostat on head and neck squamous cell carcinoma (HNSCC) cell lines. Methods: The cytotoxicity of resminostat and cisplatin on HNSCC cell lines SCC25, CAL27, and FaDu was determined using CCK‐8 cell proliferation assay and combination index analysis. Cells were irradiated with 2 to 8 Gray. Apoptosis was measured using flow cytometry and expression of Mcl‐1, p‐AKT, and survivin was investigated. Results: Treatment with resminostat showed a decrease of cell proliferation of HNSCC cell lines. In addition, a synergistic effect with cisplatin as well as with radiation treatment could be observed. Induction of cell death and dose‐dependent downregulation of survivin was evident in all cell lines. Conclusion: Resminostat is a promising treatment of HNSCC because of its antiproliferative, chemosensitizing, and radiosensitizing effects. © 2017 Wiley Periodicals, Inc. Head Neck 39: 900–907, 2017